DERMATOGLYPHIC FEATURES OF THE MЕN’S FEET IN DIFFERENT CISCARPATHIAN ETHNO-TERRITORIAL GROUPS - Gunas, I.V.; Dunaev, O.V.; Popadynets, O.G.; Kozovіy R.V.; Кіндратів, Е.О. (World of Medicine and Biology, 2020)
In the course of the study, we analyzed the ridge, delta count and the frequency of dermatoglyphic parameters located on the plantar surfaces of the feet, studied the correlations between the pattern type and ridge and delta counts. It is established that between dermatoglyphic signs of feet in men of different ethno-territorial groups of Prykarpattia (Boyks, Lemkos, Hutsuls) there are differences that allow to differentiate these ethno-territorial groups: Hutsuls have a low numerical value of the ridge count, no whorl and high frequency of loop patterns; for Boykоs it is a low numerical value of the delta account and a low frequency of whorl patterns; for Lemkos it is a high numerical value of the ridge and delta account, a significant frequency of whorl patterns.